Kinetics and binding properties of cloramphenicol imprinted polymers - Corton, Eduardo (2007)
Molecularly imprinted polymers (MIPs) are easily obtained by a non-covalent approach through the copolymerisation of suitable functional monomers and cross-linkers in the presence of the print molecule. Removal of the template leaves a polymer that selectively recognises it. However, experimental data have demonstrated that non-covalent molecularly imprinted polymers exhibit a heterogeneous binding sites distribution. In this work, two different imprinted polymers for chloramphenicol (CAP), obtained using different template concentrations, were evaluated for their kinetics and affinity binding properties against CAP in a batch approach. Experimental binding isotherms were fitted to Langmuir, Freundlich and Langmuir-Freundlich isotherms and the affinity distribution corresponding to the Freundlich isotherm was used to extract binding parameters. Parallel studies were performed for the binding of chloramphenicol diacetate to the CAP-imprinted polymers.